COMPARISON OF ENALAPRIL AND PERINDOPRIL IN PATIENTS WITH ARTERIAL HYPERTENSION AND LEFT VENTRICLE SYSTOLIC DYSFUNCTION - Yu. I. Grinshtein; O. L. Barbarash; D. A. Yakhontov; A. E. Popelysheva; V. V. Shabalin; N. B. Osetrova (Рациональная фармакотерапия в кардиологии)
Aim. To compare efficacy of enalapril and perindopril in patients with arterial hypertension (HT) and left ventricle systolic dysfunction.Material and methods. Patients (n=51) with HT and left ventricle systolic dysfunction (ejection fraction<45%) were included in the prospective open randomized comparative study. Patients were randomized into 2 groups of therapy with enalapril 10-20 mg BID (n=25) or with perindopril 4-8 mg OD (n=26). Hydrochlorothiazide (12,5-25 mg OD) was added in case of ineffective therapy. Routine clinical examination, ambulatory blood pressure (BP) monitoring, an electrocardiogram, an echocardiography were performed in all patients.Results. The 24-hour and night antihypertensive effect of enalapril was more prominent than this of perindopril. Target BP level was reached in 21 patients (84%) of enalapril group and in 20 patients (76,9%) of perindopril group. 8 (30,8%) patients of perindopril group did not reach night target BP level vs 3 (12%) patients of enalapril group. Similar improvement of the left ventricle systolic function was observed in both groups.Conclusion. Enalapril and perindopril demonstrated comparable antihypertensive and cardioprotective effect.